Celebrity Face Recognition using Deep Learning - Nur Ateqah Binti Mat Kasim; Nur Hidayah Binti Abd Rahman; Zaidah Ibrahim; Nur Nabilah Abu Mangshor (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Face recognition is one of the well studied problems by researchers in computer visions.  Among the challenges of this task are the occurrence of different facial expressions like happy or sad, and different views of the images such as front and side views.  This paper experiments a publicly available dataset that consists of 200,000 images of celebrity faces. Deep Learning technique is gaining its popularity in computer vision and this paper applies this technique for face recognition problem.  One of the techniques under deep learning is Convolutional Neural Network (CNN).  There is also pre-trained CNN models that are AlexNet and GoogLeNet, which produce excellent accuracy results.  The experimental results indicate that AlexNet is better than basic CNN and GoogLeNet for face recognition.